2021
DOI: 10.1109/access.2021.3050545
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of SOA on An Asynchronous ERP and VEP-Based BCI

Abstract: Our previous study established an asynchronous BCI system by using the oddball paradigm to simultaneously induce event-related potentials (ERPs) and visual evoked potentials (VEPs) (E-V BCIs). We found that stimulus onset asynchrony (SOA) is an important factor for performance since it significantly affects the ERP and VEP. Increasing the SOA increases the ERP, which improves the accuracy of detecting target stimuli. However, a larger SOA leads to a lower VEP frequency, which causes the VEP to have poor accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…The positivity found at around 350–600 ms, which was generalized across the entire scalp surface, was probably a P300 signal, the component that gives its name to this type of BCI system (i.e., a P300 speller). This positivity has been also reported at similar temporal intervals in several other studies (e.g., by Kellicut-Jones and Sellers [ 15 ] and M. Li et al [ 32 ]). The negativity found for the occipital areas (PO7, PO8, and Oz) at around 280 ms could be an N170 signal (e.g., Kaufmann et al [ 16 ], Q. Li et al [ 17 ], and Lu et al [ 33 ]).…”
Section: Discussionsupporting
confidence: 87%
“…The positivity found at around 350–600 ms, which was generalized across the entire scalp surface, was probably a P300 signal, the component that gives its name to this type of BCI system (i.e., a P300 speller). This positivity has been also reported at similar temporal intervals in several other studies (e.g., by Kellicut-Jones and Sellers [ 15 ] and M. Li et al [ 32 ]). The negativity found for the occipital areas (PO7, PO8, and Oz) at around 280 ms could be an N170 signal (e.g., Kaufmann et al [ 16 ], Q. Li et al [ 17 ], and Lu et al [ 33 ]).…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, compared to relevant discussion in [17] which assumed equal target and non-target likelihoods, the present RSVP design possessed unequal classes. As well, while previous reports described changes to ERP attention effects with increasing SOI durations, the present study used dramatically shorter latencies overall than [18], and another comparison of different SOA values on ERPs and VEPs did so using a block design [26]. Increasing N200 and P300 amplitudes observed in that study and a lack of such effects in the present study might be explained by our use of uniform random distributions, which result in an unchanging mean SOI value across conditions.…”
Section: Adjacent Erp Overlap Jittered Soi and Ssvepsupporting
confidence: 43%
“…In the context of this investigation, "attention" is defined as selective visual attention to the presentation of a target letter stimulus. Likewise, SOI refers to the time elapsed between the onset of two sequential stimuli, which some groups refer to instead as stimulus onset asynchrony (SOA) [11,26]. Our study analyzed three EEG-based signals known to be evident during RSVP: N200, P300, and alpha attenuation [11,19].…”
Section: Aims and Hypothesesmentioning
confidence: 99%
“…Specifically, our results regarding the amplitude difference showed that the distinguishing potentials between target and non-target stimuli are N200 and P300. Both potentials have previously been employed in the literature for ERP-BCI applications and have been manipulated—using different stimuli or SOA—to enhance system performance [ 41 , 42 ]. In our study, the differences in the ERP waveform related to amplitude difference were more affected in terms of latency rather amplitude.…”
Section: Discussionmentioning
confidence: 99%